Taking Concerns Into Account: Understanding The Technology Adoption Process From The Esl Teachers’ Point Of View - Norazila, Abd Aziz (Malaysian English Language Teaching Association, 2008)
The dual emphasis on technology literacy and English Language profi ciency as prerequisites for Malaysia’s successful participation in the new global economy has elevated the need to reconsider the role of technological innovations in English Language Teaching. This study addresses the need to understand the concerns expressed by teachers pertaining to technology adoption in order to facilitate institutionalization of technology in ESL instruction. By understanding the adoption process from the teachers’ point of view, intervention measures relevant to the instructional context of the teachers can be better designed and developed. Using the Concerns-Based Adoption Model (CBAM) as the theoretical framework, fi ndings of this study show that ESL teachers express technology adoption concerns characteristic of those of the typical non-user. The fi ndings also indicate that the number of years which ESL teachers have in terms of technological adoption experience has no signifi cant effect on resolving their self concern issues. Results of a one-way MANOVA further show no signifi cant difference in terms of the level of self-concern intensity between the teachers who had and had not attended professional development programs on ICT integration. It is thus argued that efforts to facilitate adoption and institutionalization of technological innovations in ESL instruction must go beyond deployment of technological infrastructure or making ICT training a requirement for all. If left unattended and unresolved, teachers’ continuous struggle with self-concern issues may inevitably become the cause for the discontinued use of technological innovations in their ESL practices.